Her every fear [compact disc, unabridged] - Swanson, Peter, 1968- (Blackstone Audio ; HarperAudio, 2017)
"Kate Priddy was always a bit neurotic, but after an ex-boyfriend kidnapped her and nearly ended her life, her bouts of anxiety began exploding into full-blown panic attacks. When Corbin Dell, a cousin in Boston, suggests the two temporarily swap apartments, Kate agrees, hoping that time away in a new place will help her overcome the past traumas of her life. But at Corbin's grand apartment on Beacon Hill, Kate makes a shocking discovery: his next-door neighbor, a young woman named Audrey, has been murdered. When the police question her about Corbin, a shaken Kate has few answers, but many questions of her own--and her curiosity intensifies when she meets Alan, a handsome tenant who lives across the courtyard. Alan saw Corbin surreptitiously come and go from Audrey's place, yet Corbin's denied knowing her. Then, Kate runs into a man claiming to be the dead woman's old boyfriend, who insists Corbin did the deed. Corbin proclaims his innocence and calms Kate's nerves ... until she comes across disturbing objects hidden in the apartment. Could Corbin really be a killer? And what about Alan? Kate finds herself drawn to this appealing man who seems so sincere, but she isn't sure. Jet-lagged and emotionally fragile, her imagination full of dark images, Kate can barely trust herself, let alone a stranger she's just met. Yet the danger Kate imagines isn't nearly as twisted as what is about to happen. When her every fear becomes very real. And much, much closer than she thinks."--Container.